The Role of Financial Technology in Improving Financial Literacy for MSME Actors - Zaky, Muhammad; Zainuddin Hamidi, Dendi (KnE Social Sciences, 2022)
MSMEs play a strategic role in improving a country’s economy. This can be seen through the contribution of MSMEs in increasing Indonesia’s GDP. As a pillar of the country’s economy, MSMEs must adapt to financial technology for providing easier access to financial services so that the MSME actors can have financial literacy competencies. Therefore, this study examines the effect of financial technology on the financial literacy. The associative quantitative method is used for parsing research problems based on urgency. A survey was conducted on 100 respondents of MSME actors. The data analysis test was carried out with the instrument quality test stages, and various basic assumptions had been fulfilled so that the research results were not biased. A bivariate regression analysis method was used. The results show that financial technology have a significant effect on financial literacy. Keywords: financial technology, financial literacy